How Does Grit Relate to The Psychological Well-being of Students Who Are Writing Thesis? - Shiddiqoh, Farah; -, Komarudin (Universitas Trunojoyo Madura, 2025)
In compiling and writing an undergraduate thesis, final-year students tend to encounter several problems. Those problems will come with pressure both from outside and from within, resulting in students' personality factors not being achieved, where in advance, these conditions trigger disruption of students' psychological well-being. Final-year students who are writing a thesis need to have a personality in the form of